New mechanistic insights into the RAS-SIN1 interaction at the membrane - Pudewell, Silke; Lissy, Jana; Nakhaeizadeh, Hossein; Mosaddeghzadeh, Niloufar; Nakhaei-Rad, Saeideh; Dvorsky, Radovan; Ahmadian, Mohammad R. (Frontiers in Cell and Developmental Biology, 2022)
Stress-activated MAP kinase-interacting protein 1 (SIN1) is a central member of the mTORC2 complex that contains an N-terminal domain (NTD), a conserved region in the middle (CRIM), a RAS-binding domain (RBD), and a pleckstrin homology domain (PH). Recent studies provided valuable structural and functional insights into the interactions of SIN1 and RBD with RAS proteins. However, the mechanism for a reciprocal interaction of the RBD-PH tandem with RAS proteins and membrane as upstream events to spatiotemporal mTORC2 regulation is not clear. The biochemical assays in this study led to the following results: (i) all classical RAS paralogs, including HRAS, KRAS4A, KRAS4B, and NRAS, can bind to SIN1-RBD in biophysical and SIN1 full-length (FL) in cell biology experiments; (ii) the SIN1-PH domain modulates interactions with various types of membrane phosphoinositides and constantly maintains a pool of SIN1 at the membrane; and (iii) a KRAS4A-dependent decrease in membrane binding of the SIN1-RBD-PH tandem was observed, suggesting for the first time a mechanistic influence of KRAS4A on SIN1 membrane association. Our study strengthens the current mechanistic understanding of SIN1-RAS interaction and suggests membrane interaction as a key event in the control of mTORC2-dependent and mTORC2-independent SIN1 function.